PSIKOEDUKASI PENDIDIKAN SEKSUALITAS UNTUK MENINGKATKAN PENGETAHUAN REMAJA SMP DAN SMA SAINT JOHN’S CATHOLIC SCHOOL GADING SERPONG, TANGERANG - Penny Handayani; Laurentius Sandi Witarso; Yuvens Marvel Yanggah; Melisa Vitalia Fransiska (Jurnal Bakti Masyarakat Indonesia, 2026)
Adolescence is a transitional period from childhood to adulthood marked by biological changes and the development of identity. Without adequate understanding, adolescents are at risk of facing various problems such as sexual violence and sexually transmitted diseases. Therefore, comprehensive sexuality education is essential to help adolescents protect themselves and make healthy decisions. However, this topic remains taboo in some contexts, leading adolescents to seek misleading information. A sexuality education seminar was held on August 8, 2025, at Saint John’s Catholic School Gading Serpong. The school upholds core values such as Respect, Responsibility, Resilience, Integrity, Generosity, Harmony, and Truth, aiming to balance students’ academic and personal growth. To support these values, the seminar was designed to equip junior and senior high school students with knowledge about puberty and skills to protect themselves in social interactions. The seminar was conducted using a psychoeducational approach, combining knowledge and practical skills related to relevant sexuality issues. Sessions were separated by gender (male and female) and educational level (junior and senior high school) to address biological differences. The program’s effectiveness was evaluated using a paired t-test to compare participants’ pre-test and post-test results. Out of 207 male and 151 female students who attended, 112 males and 86 females completed the evaluation. Findings showed a notable increase in sexuality knowledge, though the results did not represent all participants. Future programs are expected to include follow-up evaluations to assess sustained knowledge and attitude changes among students.